Evaluation of Different Additives on Mechanical Properties and Performance of Hot Mix Asphalt Using Marshall Stability and ITSM Tests - Utku Tiryaki, Sefa; Yalcin, Erkut (ISRES Publishing, 2025)
This study comprehensively evaluated the mechanical performance of hot mix asphalt (HMA) mixtures prepared with neat and modified binders using Marshall stability and Indirect Tensile Stiffness Modulus (ITSM) tests. Marshall stability test results revealed that the incorporation of polymeric and reactive additives increased the stability values of the mixtures compared to those produced with neat binder. Among the additives investigated, the 611 elastomer demonstrated the highest improvement in stability, achieving up to 1.80 times higher values than the neat mixture. Other additives, such as 701, SBS, and CR, also enhanced stability, albeit to varying extents. The ITSM test results indicated that the stiffness modulus of the mixtures increased with higher elastomer content. The 611 elastomer exhibited the most significant impact on stiffness among the tested elastomers, while 701 and SBS showed comparable performance. Furthermore, higher ITSM test temperatures resulted in decreased stiffness values across all mixtures. The number of load repetitions required to initiate cracking was found to be lowest in the mixtures containing neat binder and highest in mixtures containing 4% of the 611 elastomer, indicating superior fatigue resistance. Overall, both Marshall and ITSM tests confirmed that modified binders, particularly those incorporating the 611 elastomer, significantly enhance the mechanical properties of HMA mixtures, improving their resistance to deformation and cracking under load. © 2025 Published by ISRES Publishing: www.isres.org.
5th International Conference on Basic Sciences and Technology, ICBAST 2025 -- 28 August 2025 through 31 August 2025 -- Budapest -- 344359
Keywords: Hot mix asphalt; Indirect tensile stiffness modulus; Marshall stability; Modified bitumen